Transcriptional dynamics orchestrating the development and integration of neurons born in the adult hippocampus - Rasetto, Natalí B.; Giacomini, Damiana; Berardino, Ariel A.; Waichman, Tomás Vega; Beckel, Maximiliano S.; Di Bella, Daniela J.; Brown, Juliana; Davies-Sala, M. Georgina; Gerhardinger, Chiara; Lie, Dieter Chichung; Arlotta, Paola; Chernomoretz, Ariel; et al. (Science Advances, 2024)
The adult hippocampus generates new granule cells (aGCs) with functional capabilities that convey unique forms of plasticity to the preexisting circuits. While early differentiation of adult radial glia-like cells (RGLs) has been studied extensively, the molecular mechanisms guiding the maturation of postmitotic neurons remain unknown. Here, we used a precise birthdating strategy to study aGC differentiation using single-nuclei RNA sequencing. Transcriptional profiling revealed a continuous trajectory from RGLs to mature aGCs, with multiple immature stages bearing increasing levels of effector genes supporting growth, excitability, and synaptogenesis. Analysis of differential gene expression, pseudo-time trajectory, and transcription factors (TFs) revealed critical transitions defining four cellular states: quiescent RGLs, proliferative progenitors, immature aGCs, and mature aGCs. Becoming mature aGCs involved a transcriptional switch that shuts down pathways promoting cell growth, such SoxC TFs, to activate programs that likely control neuronal homeostasis. aGCs overexpressing Sox4 or Sox11 remained immature. Our results unveil precise molecular mechanisms driving adult RGLs through the pathway of neuronal differentiation.
CRIS-Team Scopus Importer:2024-08-02